Rapid Aspect-Oriented Assessment of Relational Database Design Assignments - Ajanovski, Vangel V. (ACM, 2022)
It can be argued that assignments in a Databases course, where students are required to build a database instance based on specifications provided in the form of Entity-Relationship Diagrams and descriptions, are one of the best ways to evaluate students’ practical knowledge because they simultaneously cover a variety of topics and cognitive levels. Organizing an exam with such assignments is a time-consuming process, even more so in a large course. This work proposes a rapid aspect-oriented assessment process and presents a software system that automates most of the tasks needed to administer and assess an exam that includes such assignments.